Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/293687
|View full text |Cite
|
Sign up to set email alerts
|

The Influence ofBMXGene Polymorphisms on Clinical Symptoms after Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) is one of the most common neurological disorders. Most patients diagnosed with mTBI could fully recover, but 15% of patients suffer from persistent symptoms. In recent studies, genetic factors were found to be associated with recovery and clinical outcomes after TBI. In addition, results from our previous research have demonstrated that the bone marrow tyrosine kinase gene in chromosome X (BMX), a member of the Tec family of kinases, is highly expressed in rats with TBI. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Study design varied. Fifty-four publications described prospective cohort studies 16 , 17 , 19–24 , 26 31 , 34 , 35 , 37 , 38 , 40–44 , 46 53 , 55 , 57–64 , 66 – 69 , 71 , 73–80 , 83 Fourteen studies were retrospective cohort studies on banked DNA samples 18 , 25 , 32 , 33 , 36 , 39 , 45 , 54 , 56 , 65 , 70 , 72 , 82 , 83 Study location also varied significantly, with the most commonly reported country of origin being the United States ( n = 43). Twenty-six studies included fewer than 100 patients 17 , 19 , 24 , 26 , 27 , 32 , 35 , 37 , 40 , 42–44 , 47 , 50–53 , 57 , 67–69 , 71 , 74 , 76 , 78 , 80 Seven studies were published conference abstracts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study design varied. Fifty-four publications described prospective cohort studies 16 , 17 , 19–24 , 26 31 , 34 , 35 , 37 , 38 , 40–44 , 46 53 , 55 , 57–64 , 66 – 69 , 71 , 73–80 , 83 Fourteen studies were retrospective cohort studies on banked DNA samples 18 , 25 , 32 , 33 , 36 , 39 , 45 , 54 , 56 , 65 , 70 , 72 , 82 , 83 Study location also varied significantly, with the most commonly reported country of origin being the United States ( n = 43). Twenty-six studies included fewer than 100 patients 17 , 19 , 24 , 26 , 27 , 32 , 35 , 37 , 40 , 42–44 , 47 , 50–53 , 57 , 67–69 , 71 , 74 , 76 , 78 , 80 Seven studies were published conference abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies documented the relationship between various SNPs and nonglobal patient outcomes (i.e., neuropsychiatric, behavioral, and other). 57 , 60 , 66 , 67 , 69 , 71–73 , 82 , 83 The targets for these polymorphisms included: ACE, 57 various oxytocin SNPs, 66 PERIOD3, 67 ATP binding cassette, 60 nitric oxide synthase-3 (NOS3), 69 alpha synuclein (SNCA), 71 kidney and brain expressed protein (KIBRA), 72 BMX, 73 methyenetetrahydrofolate reductase (MTHFR), 82 and adenosine A1 receptor. 83 Full details can be found in Supplementary Appendix 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphism results from a substitution, deletion, or insertion of a base in the genetic code. [42][43][44][45][46] The 2 most studied types of epigenetic changes that influence recovery from TBI (often in animal models) involve methylation, when a molecule of DNA is capped by a methyl group that prevents transcription (essentially turning the gene "off"). Emerging research on combat veterans associates PTSD with decreased amounts of methylation (hypomethylation) on the promoter region of glucocorticoid receptor genes, although there was no controlling for the confounding variable of TBI in this sample.…”
Section: Genomic Variations Affecting Outcomesmentioning
confidence: 99%
“…SNP results from a substitution, deletion, or insertion of a base in the genetic code. [42][43][44][45][46] The two most studied types of epigenetic changes that influence recovery from TBI (often in animal models) involves methylation, when a molecule of DNA is capped by a methyl group that prevents transcription (essentially turning the gene "off").…”
Section: Genomic Variations Affecting Outcomesmentioning
confidence: 99%